Unveiling micro internal short circuit mechanism in a 60 Ah high-energy-density Li-ion pouch cell. (June 2021) - Qi, Xiaopeng; Liu, Bingxue; Pang, Jing; Yun, Fengling; Wang, Rennian; Cui, Yi; Wang, Changhong; Doyle-Davis, Kieran; Xing, Chaojian; Fang, Sheng; Quan, Wei; Li, Bin; et al.
Abstract: The identification, evaluation, and prevention of micro internal short circuits (ISCs) are crucial for the safety of large-capacity high-energy-density (HED) Li-ion cells. However, the evolution mechanism and the premonitory signals of the micro ISCs are not yet completely understood. Via a high-precision penetration test and accelerating rate calorimetry, we successfully trigger and investigate on-demand ISCs on a 60 Ah HED (≥ 290 Wh kg –1 ) Li-ion pouch cell with Si-based anode/Ni-rich cathode couple. Detailed behaviors of the cell components during micro ISCs, such as pinhole and crack formation, pore-closing, and rupture of the separators, as well as the destruction of positive electrodes and fusion of Al current collectors, are observed. Moreover, the correlation of these internal effects with external cell signals is identified. We demonstrate that voltage change signals, even at millivolt level, are noteworthy and can be used as premonitory signals for early warning of micro ISCs and leading indicators for predicting cell thermal runaway. The disclosed micro ISC propagation, alleviation, and acceleration mechanisms could guide the design of safe HED Li-ion cells. Graphical Abstract: This work investigates the mechanisms and safety risks of micro internal short circuits in a 60 Ah high-energy-density (> 290 Wh kg –1 ) Li-ion pouch cell via a high-precision penetration test and accelerating rate calorimetry test. ga1 Highlights: The micro ISC evolution mechanism in a 60 Ah Li-ion cell is uncovered. Detailed behaviors of cell internal components during micro ISCs are observed. The external voltage and temperature signals during micro ISCs are elucidated.